Softening by electrochemical reaction-induced dislocations in lithium-ion batteries - Ma, Z.; Xie, Z.; Wang, Y.; Lu, Chunsheng (Elsevier, 2017)
© 2016 Acta Materialia Inc. Electrodes softening during lithium insertion may result in degeneration of their electrochemical performances. In this paper, based on a coupling multiple-slip crystal plasticity formulation with three (i.e., statistically-stored, geometrically-necessary and electrochemical reaction-induced) dislocation densities, a relationship is built up between hardness and the state of charge for electrodes in lithium-ion batteries, which can take into account the indentation size effect during charging and discharging progresses. It is shown that the relationship is helpful in monitoring the state of charge and providing new avenues for applications of high-performance rechargeable batteries.